9c+6=15

Simple and best practice solution for 9c+6=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9c+6=15 equation:


9c+6=15

We simplify the equation to the form, which is simple to understand
9c+6=15

We move all terms containing c to the left and all other terms to the right.
+9c=+15-6

We simplify left and right side of the equation.
+9c=+9

We divide both sides of the equation by 9 to get c.
c=1

See similar equations:

| -1+8(8+7n)=2+56n | | 25=4(m-3)-3 | | 4-1.8y=-5.9 | | -74+4x+3x=115 | | 15r=3(r+28) | | -44n=-4n-8(3n-5) | | 6q=24q+1 | | (4x^3-8x^2+x-5)(x^2+6x)=0 | | 5(6x+4)+1=21-3x | | 11z=20-9z | | 5.7t+2.52=52.77 | | -4.3-0.1h=-6.1 | | 2(a+6)+3a=32 | | -7.32=8.8-6.2t | | 13k=19k+12 | | 0.03+420= | | -16=4c+6 | | 6(x-2)=5 | | 7x-20=3x+10 | | 2(5+-4)=12t | | 11r+4=9r+8 | | 2(-6b+6)=-8(b-3) | | (x^2-x+9)(x^2-5x)=0 | | 2(1-5k)=-5k-28 | | 0.6(a+2)=2.5 | | 37=14m+93 | | X^2-2x-12= | | f(9)=2x-4 | | 4x+2x=10+x | | 18g+483=21g+462 | | 320(5)-32(5)= | | 11x-[3x+(-1+3x)]=-66x |

Equations solver categories